A descriptive study on the occurrence of oral symptoms following the use of 3,4-methylenedioxymethamphetamine - Somera, Corinne Paz J.
MDMA or more commonly known as the drug Ecstasy is gaining popularity among teenagers and young adults. Studies show that the drug can cause oral symptoms like teeth grinding, dry mouth, jaw tension, or teeth clenching, dehydration, muscle stiffness or pain along the jaw region, teeth sensitivity, canker sores and tooth wear. At present, no local studies have been documented regarding the occurrence of these oral symptoms. It was then the objective of the study to identify oral symptoms brought about by Ecstasy use among teenagers and young adults aged 13-36 years old in Metro Manila, Philippines. The study undertaken was a descriptive study which had 41 subjects who take or have taken the drug Ecstasy at the time of the research. All the subjects answered a questionnaire but only 24 agreed to an oral examination in which the amount of tooth wear was measured using the tooth wear index.* Results show that teeth grinding (78.05%), dehydration (70.75%) and dry mouth (58.54%) are the top 3 common oral symptoms. Sixteen out of the 24 subjects who underwent oral examination had tooth wear, the mean tooth wear score was 0.075. As compared to Milosevic's findings which were 0.63 for MDMA users and 0.16 for non-users, the resulting tooth wear index score if 0.075 appear quite insignificant and thus, normal physiologic wear may be considered.